Speciation of Zn in Arid Soils With Saline Accumulations. Case Study of the Biskra Region, Algeria - Degui, Nouara; Djili, Kaddour; Daoud, Youcef; Belghemmaz, Salah (REVISTA TERRA LATINOAMERICANA, 2024)
Zinc (Zn) deficiency in plants is closely related to its bioavailability in soil. However, the behaviour of Zn in soils, especially in saline areas, remains complex. This research aims to clarify the distribution and dominant forms of Zn in arid soils with salt accumulations from the Biskra region by studying soil samples from ten representative profiles. Soil samples were collected from dif ferent horizons of each profile to a depth of 120 cm and subjected to speciation analysis using sequential extraction. The results indicate a deficiency of Zn in all soil samples, resulting in reduced concentrations of dif ferent forms of Zn. The dominant forms were residual Zn (R-Zn) and oxide-bound Zn (O-Zn), which accounted for over 90% of total Zn. The study revealed a negative correlation between soil salinity and all Zn forms, except for R-Zn, which showed a positive correlation. Additionally, Zn concentrations showed a negative correlation with gypsum, except for exchangeable Zn (E-Zn). It is important to note that the presence of gypsum in soils was significantly and negatively correlated with O-Zn. Although the sequential extraction method used may have limitations in accurately quantifying all forms of Zn, this study fills a gap in the literature on Zn assessment and speciation in arid soils. The study emphasizes the significance of soil characteristics, particularly salinity and gypsum content, in shaping Zn distribution. Overall, these results contribute to a better understanding of Zn availability and mobility in arid and saline environments, providing valuable insights for improved soil management practices in such regions.